2020
DOI: 10.1177/0300985820963087
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor-2 Is Associated With Adverse Outcomes in Canine Mammary Carcinoma

Abstract: Protease-activated receptor-2 (PAR2) is a G protein–coupled receptor that is activated by serine proteases. In humans, PAR2 is highly expressed in various cancers, including breast cancer, and is associated with cancer progression and metastasis. However, the expression and roles of PAR2 in canine mammary carcinoma remain unclear. The purpose of this study was to examine the expression of PAR2 in canine mammary carcinoma, the association between PAR2 expression and clinical characteristics, and the role of PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Statistics = linear mixed model with Benjamini-Hochberg.in the human in vitro model with sex differences observed between male and female samples 18. In the canine model, Kaji et al and Kim et al identified a role for PAR2 in canine mammary carcinoma and atopic dermatitis, respectively 44,45. However, outside of the present study, little research has explored PAR2 effects on the inflammatory response of canine IVD cells.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Statistics = linear mixed model with Benjamini-Hochberg.in the human in vitro model with sex differences observed between male and female samples 18. In the canine model, Kaji et al and Kim et al identified a role for PAR2 in canine mammary carcinoma and atopic dermatitis, respectively 44,45. However, outside of the present study, little research has explored PAR2 effects on the inflammatory response of canine IVD cells.…”
mentioning
confidence: 63%
“… 18 In the canine model, Kaji et al and Kim et al identified a role for PAR2 in canine mammary carcinoma and atopic dermatitis, respectively. 44 , 45 However, outside of the present study, little research has explored PAR2 effects on the inflammatory response of canine IVD cells. An inability to account for sex differences due to our sample size or dose of PAR2A chosen may explain why we did not see an effect of PAR2A on the canine immune modulatory pathway.…”
Section: Discussionmentioning
confidence: 95%